Analisis Kualitas Pelayanan Administrasi Prodi Manajemen Pelabuhan Dan Logistik Maritim Universitas Negeri Jakarta - Darmawan, Kaysar Wahyu (Peneliti.net, 2024)
This research aims to analyze the quality of administrative services for the Port Management and Maritime Logistics Study Program (MPLM) using quantitative descriptive methods. The instrument used was a student satisfaction questionnaire. The research population is all active students of the MPLM Study Program. The research sample was taken from MPLM students class of 2022 using a simple random sampling technique. Student satisfaction is measured through student perceptions (perceived service) of the quality of academic services which include tangibles, reliability, responsiveness, assurance, and empathy. To measure respondents' answers, a Likert scale is used which is divided into 5 scales. It is hoped that this research can provide input for the MPLM Study Program in improving the quality of its administrative services so that it can provide better satisfaction to its students.